Media and public shaming: drawing the boundaries of disclosure - Petley, J (Reuters Institute for the Study of Journalism, 2013)
The media today, and especially the national press, are frequently in conflict with people in the public eye, particularly politicians and celebrities, over the disclosure of private information and behaviour. Historically, journalists have argued that ‘naming and shaming’ serious wrong-doing and behaviour on the part of public officials is justified as being in the public interest. However, when the media spotlight is shone on perfectly legal personal behaviour, family issues and sexual orientation, and when, in particular, this involves ordinary people, the question arises of whether such matters are really in the ‘public interest’ in any meaningful sense of the term. In this book, leading academics, commentators and journalists from a variety of different cultures, consider the extent to which the media are entitled to reveal details of people’s private lives, the laws and regulations which govern such revelations, and whether these are still relevant in the age of social media.